2003
DOI: 10.1046/j.1365-2389.2003.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al hydroxide polymers on cation exchange of montmorillonite

Abstract: Summary Al hydroxide polymers (AlHO) can significantly influence the cation exchange behaviour of clays. We have determined the effect of synthesized AlHO on Ca–Na, Zn–Na and Pb–Na exchange for a series of exchanger compositions and two Al loadings at pH 6.0 and an ionic strength of 0.01 m. The preference for Ca on the siloxane surface of the clay–AlHO system (CAlHO) was greater than for the pure clay, and the average KV (Vanselow selectivity coefficient) was determined to be 2.16 and 1.24, respectively. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…The lowest Kne values were detected in the soils with the lowest clay contents due to the predominance of kaolinite and HIV in the clay fraction. Although the HIV is a 2:1 clay mineral with functional groups of permanent charges, the interlayers are partially or totally blocked by the Al polymers, preventing their interaction with the ions of the soil solution (Dixon and Weed 1989;Janssen et al 2003).…”
Section: Non-exchangeable Potassium (Kne) In the Soils And In The Silmentioning
confidence: 99%
“…The lowest Kne values were detected in the soils with the lowest clay contents due to the predominance of kaolinite and HIV in the clay fraction. Although the HIV is a 2:1 clay mineral with functional groups of permanent charges, the interlayers are partially or totally blocked by the Al polymers, preventing their interaction with the ions of the soil solution (Dixon and Weed 1989;Janssen et al 2003).…”
Section: Non-exchangeable Potassium (Kne) In the Soils And In The Silmentioning
confidence: 99%
“…The sorption of Zn to HIS as a function of hydroxy-Al loading, solution pH, and Zn concentration has previously been studied by Janssen and coworkers (Janssen et al, 2003a;Janssen et al, 2003 b). They found that the formation of hydroxy-Al interlayers reduces the cation exchange capacity, but provides high-affinity sorption sites for Zn.…”
Section: Sorption Of Zn In Hydroxy-interlayered Mineralsmentioning
confidence: 99%
“…It has a N 2 -BET surface are of $31 m 2 /g similar to the Wyoming montmorillonite SWy-2 ( van Olphen and Fripiat, 1979;Bradbury and Baeyens, 1998), which has been used in the current study and the work by Scheinost et al (2002). Thus, the results from Zn uptake studies by Janssen et al (2003a) can be compared to the local coordination of Zn derived from EXAFS data obtained with a similar clay mineral.…”
Section: Sorption Of Zn In Hydroxy-interlayered Mineralsmentioning
confidence: 99%
“…Their surface properties and stability have been extensively studied [11][12][13]. Interactions between polymeric cations and clays may significantly influence surface properties of the pristine clays [11,12,14,15]. Given the high reactivity, large surface areas and high positive charges of HyAl and HyFe cations, Mt-complexes may play a significant role in regulating the mobility of P and some potential anionic pollutants such as arsenate and selenite.…”
Section: Introductionmentioning
confidence: 99%